Measuring the Quality of Health Services in the Benghazi Center for diagnosis and treatment of diabetes، from the Point of View Reviewers - Omar, Fatimah Abdullah Atitat Allah; Tarani, Faten Ali; Obaid, Hajar Muhammad Saber (Journal of medical and pharmaceutical sciences, 2019)
Seen patient satisfaction as a source of information and an effective measure to evaluate the true and judgment on the level and the reality of health care provided to them، as well as an important tool in the field of management research and planning health care and policy-related. This study aimed to measure the quality of providedhealth services at the Benghazi Center for diagnosis and treatment of diabetes from the point of view patients، also the study suggested some of recommendations that contribute to the improvement and development of the reality of services in health centers and reduce the negative effects So as to achieve benefit for the management of the center and the beneficiaries. METHODOLOGY: Study Design: This is a quantitative research study (cross-sectional، descriptive study. Setting: This study conducted in the Benghazi Center for diagnosis and treatment of diabetes. Participants: this study included (378) Diabetes The sample size was determined using Epilno7 at 95% confidence Step 80% and the percentage of error of 5%.instrument: the study collected data by using a questionnaire that consisting of two parts: a part of the data relating to the description of the sample members، the second part of the collection of data related to the evaluation of the services provided by the center، Of 22 questions divided into 5 dimensions of quality (6) questions of melody (5) questions of reliability (3) questions of response (4) questions of safety and confidence (4) questions of empathy.. RESULTS:. the study found the Benghazi center for the diagnosis and treatment of diabetes medical service dimensions are available in it in terms of responsiveness، empathy، tangible، and safety and confidence level of the average acceptance except for - reliability dimension from the point of view and reviewers، The equivalent of (3.3) recorded for both response and empathy dimensions (3.1) for tangibility dimension (3.5) safety and confidence dimensions while the reliability dimension recorded approximately (2.8).The study concluded to Work to raise the quality of health services provided to patients by focusing on the following: Conducting lectures on education and awareness on an ongoing and periodic basis on diabetes mellitus. Providing various specialities، especially as it is known to link diabetes with several complications that require the existence of different specialities. There are several physical factors stand without providing a good quality service and acceptable to patients، including the difficulty of access to the center because of the signatory must، therefore، be the decision-makers and officials to establish other centers for patients diagnosed with diabetes to reduce the burden on patients and achieve the desired benefit.
Keywords: Benghazi Diabetes Diagnostic Center; quality of health services; dimensions of quality